2018
DOI: 10.1007/s00894-018-3716-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on elastic properties of CNT-polyethylene nanocomposite and its interface using MD simulations

Abstract: This paper investigates the effect of temperature on the elastic modulus of carbon nanotube-polyethylene (CNT-PE) nanocomposite and its interface using molecular dynamics (MD) simulations, by utilizing the second-generation polymer consistent force field (PCFF). Two CNTs-armchair and zigzag-were selected as reinforcing nano-fillers, and amorphous PE was used as the polymer matrix. For atomistic modelling of the nanocomposite, the commercially available code Materials Studio 8.0 was used and all other MD simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…[23][24][25] Recently, researchers have presented a series of works on MD simulation to predict the mechanical properties of nanocomposites. 26 There were some researches on the prediction of the Young's modulus of uniaxial CNT nanocomposites, including polyethylene (PE)-based matrix, 27 polyethylene-oxide (PEO)-based matrix. 28 Due to the difficulty in fabricating continuous CNT reinforced nanocomposites (a few hundred micrometers at the most 29 ), the mechanical properties of short and random CNT reinforced nanocomposites were mostly evaluated by MD simulation, such as CNT/PE system, 30 CNT/poly(methyl methacrylate) (PMMA) system, 31 carbon nanober (CNF)/polypropylene (PP) system.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Recently, researchers have presented a series of works on MD simulation to predict the mechanical properties of nanocomposites. 26 There were some researches on the prediction of the Young's modulus of uniaxial CNT nanocomposites, including polyethylene (PE)-based matrix, 27 polyethylene-oxide (PEO)-based matrix. 28 Due to the difficulty in fabricating continuous CNT reinforced nanocomposites (a few hundred micrometers at the most 29 ), the mechanical properties of short and random CNT reinforced nanocomposites were mostly evaluated by MD simulation, such as CNT/PE system, 30 CNT/poly(methyl methacrylate) (PMMA) system, 31 carbon nanober (CNF)/polypropylene (PP) system.…”
Section: Introductionmentioning
confidence: 99%
“…33 used experimental results and comprised the stress–strain curves of PP 3371 specimens with 10% nanoclay reinforcement at −54 C, −20 C,49CCand71C, and showed that the Young’s modulus was decreased when the temperature increased. Also, Singh and Kumar 34 investigated the effect of temperature on elastic properties of CNT–polyethylene nanocomposite. Their results showed that by increasing the temperature from 100Kto400 K, the elastic modulus decreased from 2.05GPa to 0.72GPa.…”
Section: Resultsmentioning
confidence: 99%
“…Other significant factors appear to be the end cap of CNT, its diameter, and the strength of van der Waals interactions [32]. Recent MD simulations suggested that the interfacial energy and IFSS can be tuned through surface modifications of the CNT, especially hydroxyl groups at the ends [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%